Posthuman Hybridity in Leila S. Chudori’s Laut Bercerita: A Study of Digital, Ecological, and Spectral Agency - Chairuddin; Nuraini, Cut; Setiana, Diana; Zulida, Evi; Wibowo, Guntur Arie; Rahmiati (Program Studi Pendidikan Sejarah - Universitas Samudra, 2025)
This study examines Laut Bercerita (2017) by Leila S. Chudori through the lens of posthuman hybridity, focusing on the intertwined roles of digital technology, ecological environment, and spectral agency in shaping identity. Amidst the global digital era and ecological crisis, traditional anthropocentric views of human identity are challenged by fluid, relational, and distributed constructions involving human and non-human actors. Utilizing interdisciplinary theoretical frameworks including Braidotti’s posthumanism, Hayles’ digital cognition, Alaimo’s material ecocriticism, and Derrida’s hauntology, this study employs qualitative textual analysis to reveal how the novel’s characters negotiate identity across three interconnected dimensions: digital archives as extensions of memory and consciousness; the sea as an active ecological agent influencing subjectivity; and spectral presences of political trauma that haunt and shape contemporary identities. The findings demonstrate that Laut Bercerita offers a critical intervention in Indonesian post-Reformasi literature by portraying identity as hybrid and emergent from dynamic relations between technology, environment, and history. This article contributes to contemporary Indonesian literary studies by foregrounding posthuman perspectives that move beyond anthropocentrism and emphasize inclusivity in understanding subjectivity in the digital-ecological age.